Post-disruptive runaway electron beams in the COMPASS tokamak. (11th August 2015) - Vlainic, Milos; Mlynar, J.; Cavalier, J.; Weinzettl, V.; Paprok, R.; Imrisek, M.; Ficker, O.; Varavin, M.; Vondracek, P.; Noterdaeme, J.-M.
Abstract : For ITER-relevant runaway electron studies, such as suppression, mitigation, termination and/or control of a runaway beam, it is important to obtain the runaway electrons after the disruption. In this paper we report on the first discharges achieved with a post-disruptive runaway electron beam, termed a 'runaway plateau', in the COMPASS tokamak. The runaway plateau is produced by a massive gas injection of argon. Almost all of the disruptions with runaway electron plateaus occurred during the plasma current ramp-up phase. The Ar injection discharges with and without a runaway plateau were compared for various parameters. Parametrisation of the discharges shows that the COMPASS disruptions fulfil the range of parameters important for runaway plateau occurrence. These parameters include electron density, electric field, disruption speed, effective safety factor, and the maximum current quench electric field. In addition to these typical parameters, the plasma current value just before the massive gas injection proved to be surprisingly important.